Short note: Proposal for a new notation in bird field surveys with the territory mapping method for birds - Brauze, Tomasz (Ecological Questions, 2012)
The use of a new notation together with the territory mapping method is proposed for imprecisely located singing males, owing to which a position of a bird can be noted more precisely in field surveys